The Role of Psycholinguistics in English Language Learning - Naibaho, Lamhot (Eximia, 2022)
To use the language fluently and communicatively, somebody has to master the rules (grammar) and aspects of the language (cognitive, affective, and psychomotor). Most of these parts are covered in psycholinguistics. This study aims to investigate the role of psycholinguistics in English language learning. It is done through a literature review at Universitas Kristen Indonesia. The result of the study is that psycholinguistics in English language learning is very important. Psycholinguistics can help the teachers understand all of the conditions and context of learning, such as how the students listen, speak, read, and write. So from the perspective of psycholinguistics, a teacher may tackle students’ difficulties in learning English.